A comparative study on physicochemical properties and in vitro bioaccessibility of bioactive compounds in rosehip (Rosa canina L.) infusions treated by non‐thermal and thermal treatments. Issue 6 (10th November 2021) - Ozkan, Gulay; Stübler, Anna‐Sophie; Aganovic, Kemal; Draeger, Gerald; Esatbeyoglu, Tuba; Capanoglu, Esra
Abstract: The present study aimed to compare the effects of non‐thermal techniques with thermal treatment on physicochemical properties, bioaccessibility, and antioxidant capacity of bioactives in rosehip ( Rosa canina ) infusions. High pressure processing (HPP) at 200, 400, or 600 MPa for 5 and 15 min; pulsed electric field (PEF) with 5, 10, and 15 kJ/kg specific energy intakes at 1 and 3 kV/cm electric field strength; and thermal treatment (TT) at 85°C/10 min were applied. According to the results, processing method had varying effects on the contents of phenolic compounds, antioxidant capacity, and bioaccessibility in rosehip infusions. The highest retention of total phenolics (TPC) and flavonoids (TFC) were achieved by the TT (2278 mg gallic acid equivalents (GAE)/100 g dry weight (dw) and 3728 rutin equivalents (RE)/100 g dw, respectively) and HPP treatment at a pressure of 600 MPa for 15 min (2268 mg GAE/100 g dw and 3695 mg RE/100 g dw, respectively). These findings are in line with the results of antioxidant capacities of the samples. Besides, TT, HPP treatment at 600 MPa/5 min, and PEF treatment at 5 and 15 kJ/kg energy intakes (PEF1 and PEF3) resulted with a higher recovery of TPC, TFC, and antioxidant capacity after gastrointestinal digestion. It can be concluded that HPP and PEF treatments at specific conditions could be used in the processing of infusions and beverages. However, it should be considered that appropriate processing parameters should be selected and optimized for each sample individually, to assure the best nutritional value and quality characteristics. Novelty impact statement: Better retention of bioactive compounds after high pressure processing (HPP) treatment at a pressure of 600 MPa for 15 min. A noticeable improvement in the recovery of bioactive content and antioxidant capacity after HPP and pulsed electric field processing. Potential of non‐thermal food processing techniques as alternative to conventional thermal treatments in the production of functional foods with enhanced nutritional value.